2022
DOI: 10.1155/2022/5430598
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patent Foramen Ovale: Analysis from a Single Center

Abstract: Objective. To collect and analyze data of patent foramen ovale (PFO). Methods. This study included a total of 260 patients diagnosed with PFO. We analyzed basic clinical data such as sex, age, transesophageal echocardiography as well as other symptoms. Results. Our data showed that females accounted for the highest proportion of PFO (166 females, 64%), with the highest number of patients (65 patients) having between 45 and 55 years. Transesophageal echocardiography examination demonstrated frequent occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(27 reference statements)
0
3
0
2
Order By: Relevance
“… 28 The higher prevalence of migraine among women is well known; among healthy young women, the prevalence varies between 18% and 33%, whereas it is <10% in young men. 30 , 31 Also, migraine prevalence has been consistently higher among patients with PFO, 32 and several studies have shown that migraine may have a close relationship with PFO. 33 …”
Section: Discussionmentioning
confidence: 99%
“… 28 The higher prevalence of migraine among women is well known; among healthy young women, the prevalence varies between 18% and 33%, whereas it is <10% in young men. 30 , 31 Also, migraine prevalence has been consistently higher among patients with PFO, 32 and several studies have shown that migraine may have a close relationship with PFO. 33 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study have reported that PFO was associated with migraine(34%), stroke or TIA(25%), syncope(21%), chest tightness(37%), and palpitations(33%), with dizziness(63%) being the most symptom in the patients with PFO. [24] Activities increased right atrial pressure and worsened the right-to-left shunt, the symptoms of chest tightness aggravated after activities. The important clinical effect of a PFO is right-to-left shunting and the consequent potential for paradoxical embolism and arterial desaturation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Regarding echocardiographic findings, one had a diagnosis of IAC type ostium secundum with left-toright flow, considered a non-critical CHD, and seven had a report of PFO, four of which had PFO with flow from left to right, and three PFO with bidirectional flow, considered a physiological state, as under usual circumstances it closes in the first year of life. 23 These changes, when assigned a grade under the Allan and Huggon parameter, which range from 1 to 10, with 1 being the best prognosis and 10 being the worst, are classified with a grade of 2, making it possible to predict a good prognosis and low rates of morbidity and mortality in the long run. 9 PFO was also the most common finding by Carvelo et al, 24 in an analysis of positive pulse oximetry tests, totaling 40%, followed by IAC (5.7%), PFO + IAC (3.8 %), patent ductus arteriosus (3.8%), FOP + pulmonary hypertension (1.9%), FOP + patent ductus arteriosus + pulmonary hypertension (1.9%), FOP + aortic hypoplasia (1.9% ).…”
Section: Discussionmentioning
confidence: 99%